Minimal residual disease-directed therapy in acute myeloid leukemia - Kayser, Sabine (Blood, 2015)
Case 1: A 35-year-old man with a normal white blood cell (WBC) count (9.3 × 10 9 /L) was diagnosed with acute myeloid leukemia (AML) with a t(8;21)(q22;q22) translocation in 25/25 metaphases. The RUNX1-RUNX1T1 fusion gene was detected by real-time quantitative polymerase chain reaction (PCR),
Gesehen am 11.07.2017